Parenting Insight to Shape An Anti-Aggressive Behaviour - Jazariyah, Jazariyah; Jannah, Rina Roudhotul (Indonesian Journal of Islamic Early Childhood Education, 2016)
This study aimed to reveal the importance of knowledge parentingâs insight and skills of non-violence in early childhood as a manifestation of concern for child development. Parenting occupies an important position in shaping the character of children in the future. It received national attention in the world (WHO), as well as in Islam Religion. The results showed that increasing aggressiveness in juvenile cases such as bullying, fights, and fighting now is the impact on the parenting treatment with a high level of violence aggressiveness when one of them was a child. Children who are at the age of chronic and require the model in each of his behavior often become victims. Thus, in the development of children vulnerable to becoming victims or perpetrators of violence. Keywords: Parenting Insight, Anti Aggressive Behavior.